(untitled) (Comparative & International Education Series, 2021)
As the world grapples with the COVID-19 pandemic, international higher education (IHE) enters new territory and complicates models that describe the third wave of internationalization. Against this backdrop, we apply a three-layer (country, institution, individual) analysis to understand COVID-19’s impact on IHE in Canada and the United States, particularly student mobility, and consider the future of an altered landscape. At the national level, we consider how the two countries are responding to COVID-19 regarding their policies toward international students and what long-term impact might be looming. At the institutional level, we consider the pandemic’s impact on institutions’ revenue, mission, internationalization strategies, and even survival. At the individual level, we examine how this pandemic impacts international students’ plan of study in Canada and the United States, with their concern for the expense and experience of online learning and their consideration of other alternative destination countries. How to cite this chapter: O’Shea, M., Zhang, Y., & Mou, L. (2022). Reshaping the landscape considering COVID-19’s uncertain impacts on Canadian and U.S. international higher education. In R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 107-122). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/